انتشار الأمواج البنيوية ( الصوت الأول ) في بلازما فيرمي الكمية - قبلان نجاح (Latakia University Journal -Basic Sciences Series, 2016)
In this study, an Interaction Function between quasi particles has been introduced into an energy formula in Kinetic Equation of Quantum Plasmas. Such new type can be used to study quasi Particles of Quantum Fermi Plasmas, since it contains quantum term that is correlated with Bohm Potential, when the mean inter-particle distance is of the same order as the de-Broglie thermal wavelength. An interaction function between quasi particles has been expressed using spherical Functions in three-dimensional space with Landau’s spread coefficients for(l=0 ,1 ,2 ). Using such representation led to obtaining the dispersion relation of the structural waves and its energy Spectrum in balanced local condition. The use of Landau parameters in this study isconsidered new comparing to other studies in this field. It allows us to get more generic and more precise dispersion relations with new previously unknown spectrum energy in Quantum Fermi Plasmas. تم في هذه الدراسة إدخال تابع التأثير المتبادل لأشباه الجسيمات إلى صيغة الطاقة في المعادلة الحركية للبلازما الكمية، إذ يمكن استخدام نموذج جديد كهذا لدراسة أشباه الجسيمات في بلازما فيرمي الكمية التي تحتوي بالأساس على حد كمي والموافقة لجهد بوم، عندما يكون متوسط المسافة الفاصلة بين أشباه جسيمات السائل البلازمي من مرتبة طول الموجة الحرارية لــ دوبروي. تم التعبير عن تابع التأثير المتبادل بين أشباه الجسيمات، باستخدام توابع كروية في فراغ ثلاثي الأبعاد بمعاملات النشر للانداو من أجل(l=0 ,1,2 )، وباستخدام هكذا تمثيل تم الحصول على عبارات التبدد للأمواج البنيوية وطيف طاقتها في حالة التوازن الموضعي. يعد استخدام بارامترات لانداو في هذه الدراسة جديداً مقارنة مع الدراسات الأخرى في هذا المجالالذي يمكن من خلاله الحصول على عبارات تبدد أكثر شمولية ودقة مع طيف طاقة جديد غير معروف من قبل في بلازما فيرمي الكمية.